Fundus first laparoscopic cholecystectomy in patients with gall stone disease and the Fitz-Hugh-Curtis syndrome - Ale, Alexander F.; Isichei, Mercy W.; Shilong, Danaan J.; Peter, Solomon D.; Shitta, Andrew H.; Misauno, Michael A. (International Journal of Research in Medical Sciences, 2020)
Background: To present this experience using the fundus-first technique during laparoscopic cholecystectomy for the management of symptomatic gall stone disease with an intra-operative finding of Fitz-Hugh-Curtis syndrome. Methods: This is a prospective review of patients who had the fundus-first dissection during laparoscopic cholecystectomy. The study was carried out at the Jos University Teaching Hospital (JUTH), and FOMAS hospital, both of which are tertiary hospitals located in Jos. Patients were recruited from January 2017 - January 2019. All patients undergoing laparoscopic cholecystectomy who had an intraoperative diagnosis of Fitz-Hugh-Curtis syndrome, and who had the fundus-first dissection, were included in the study. Patients who had fundus-first dissection for indications other than Fitz-Hugh-Curtis syndrome, were excluded from the study. Demographic and clinical information of patients included age, sex, duration of surgery, complications, and duration of hospital stay. Descriptive statistics were applied. Results: A total of 76 patients had elective laparoscopic cholecystectomies over the study period. Of that number, 17 (22.4%) patients had an intra- operative diagnosis of Fitz-Hugh-Curtis syndrome, and had the fundus-first dissection. The mean patient age was 46.3 years (SD = 11.7 years). All patients were female. The mean operating time was 70 minutes (SD = 23 minutes). The duration of hospital stay was 24 hours. There was one conversion due to uncontrollable intraoperative bleeding. Conclusions: This study revealed that the fundus-first dissection is suitable for removing the gall bladder during laparoscopic cholecystectomy in patients with gall stone disease, and an intraoperative finding of Fitz-Hugh-Curtis syndrome.